KEBIJAKAN POLITIK ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN SIGI - Mardiono, Eko; Darwis, Darwis; Mansur, Sastrio (Katalogis, 2018)
This research uses theory of Thompson and McEwen (2006), Bargaining (bargaining), Kooptasi (cooptation), and the Coalition (the coalition), it can be concluded that the bargaining factor development programs as a result of